Kinerja Keuangan Sebelum Dan Sesudah Right Issue Di Bursa Efek Indonesia (BEI) tahun 2019-2020 (Studi Kasus Pada Sektor perusahaan Yang Terdaftar Pada BEI) - Emiliana Rachma (Sahmiyya, 2023)
This study aims to determine the effect of the Indonesian stock exchange on the company sector listed on the IDX in 2019-2020. This study uses qualitative and quantitative research methods, where the quantitative method uses normality testing to show that the data is normally distributed, then the paired sample t-test or paired test will be used to test the hypothesis and if the normality test shows that the data is not normally distributed, then the rank is marked with the Wilcoxon test. which will be used. The data sources come from journals, books and literature related to this research. It can be interpreted that the financial performance before and after the rights issue has a significant difference in the sample test conducted. The company's goal in conducting a rights issue is to increase the company's capital by obtaining additional funds from investors for the purposes of expansion, payment of maturing debt, restructuring and others. Right Issue can be said to be positive if the funds that have been obtained are invested in projects that promise high yields, whether it is a working capital increase project or a new investment project. However, a rights issue can also cause a decrease in company performance if the funds obtained from the rights issue are not managed properly. The decline in stock performance can be seen from the decline in stock prices caused by two things: first, theoretically, the rights issue offering price is lower than the prevailing stock market price, so that the post-right issue stock market price will decrease due to price adjustments. Therefore, it is IDX's duty to ensure that all transactions on the exchange run well. Thus, the IDX has an important role in supervising the trading of warrants on the stock exchange.